Mixing properties of Ni-Al liquid alloy at different temperatures - Yadav, S K; Sharma, P; Koirala, R P; Dhungana, A; Adhikari, D (BIBECHANA, 2018)
The validity of simple statistical model or simple theory of mixing has been first established by explaining the experimental values of the thermodynamic and structural properties of Ni-Al melt at 1873 K. Secondly, the linear temperature dependence of ordering energy parameter has been assumed to extend the model for predicting the mixing behaviours of the melt at different temperatures in correlation with R-K polynomials. The surface tension of the system has been explained and predicted with the help of Renovated Butler model. Theoretical investigations correspond that alloy is found to be strongly interacting or hetero-coordinating at its melting temperature. This tendency, however, gradually decreases at higher temperatures. Being more specific, the system shows ideal behaviours with respect to mixing properties at elevated temperatures. BIBECHANA 16 (2018) 106-121